Trends in the Danish work environment in 1990-2000 and their associations with labor-force changes - Burr, Hermann; Bjorner, Jakob Bue; Kristensen, Tage S.; Tüchsen, Finn; Bach, Elsa (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The aims of this study were (i) to describe the trends in the work environment in 1990-2000 among employees in Denmark and (ii) to establish whether these trends were attributable to labor-force changes. ' ' METHODS ': 'The split-panel design of the Danish Work Environment Cohort Study includes interviews with three cross-sections of 6067, 5454, and 5404 employees aged 18-59 years, each representative of the total Danish labor force in 1990, 1995 and 2000. In the cross-sections, the participation rate decreased over the period (90% in 1990, 80% in 1995, 76% in 2000). The relative differences in participation due to gender, age, and region did not change noticeably. ' ' RESULTS ': 'Jobs with decreasing prevalence were clerks, cleaners, textile workers, and military personnel. Jobs with increasing prevalence were academics, computer professionals, and managers. Intense computer use, long workhours, and noise exposure increased. Job insecurity, part-time work, kneeling work posture, low job control, and skin contact with cleaning agents decreased. Labor-force changes fully explained the decline in low job control and skin contact to cleaning agents and half of the increase in long workhours, but not the other work environment changes. ' ' CONCLUSIONS ': 'The work environment of Danish employees improved from 1990 to 2000, except for increases in long workhours and noise exposure. From a specific work environment intervention point of view, the development has been less encouraging because declines in low job control, as well as skin contact to cleaning agents, were explained by labor-force changes.
Keywords: cleaning agent; computer use; Denmark; job control; job insecurity; labor force; noise; occupational exposure; surveillance study; work environment; work posture; workhours